Nano porous rare earth silicate thermal insulation fiber synthesized by coprecipitation method and preparation method thereof

Nanoporous rare earth silicate is synthesized by co-precipitation method and blended with polymer polyester slices to prepare nanoporous rare earth silicate insulation fibers with excellent insulation performance, solving the problems of complex preparation, high cost and poor insulation effect in the prior art, and achieving efficient and economical preparation of insulation fibers.

CN119615408AActive Publication Date: 2025-03-14TIANJIN BAOGANG RES INST OF RARE EARTHS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510026002.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-14
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

In the prior art, the preparation process of rare earth silicate is complex and costly, with high thermal conductivity coefficient of insulation fibers, poor insulation effect and low fiber tensile strength.

Method used

Nanoporous rare earth silicate insulating fibers were synthesized by co-precipitation method. Nano-scale porous rare earth silicate was prepared by regulating the concentration of rare earth chloride solution, adding surfactant and adjusting the pH value of the reaction system, and blending it with polymer polyester slices, and insulating fibers were prepared through melt spinning process.

Benefits of technology

The nano-scale porous rare earth silicate is efficiently prepared, and the formed insulation fiber has low thermal conductivity, high tensile strength and excellent insulation effect. It has a light texture and is suitable for outdoor products, clothing and industrial textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615408A_ABST
    Figure CN119615408A_ABST
Patent Text Reader

Abstract

The invention provides nano-porous rare earth silicate thermal insulation fibers synthesized by a coprecipitation method and a preparation method of the nano-porous rare earth silicate thermal insulation fibers. The fibers are prepared from the following components in parts by weight through a melt spinning process: 2-15 parts of nano-porous rare earth silicate and 85-98 parts of macromolecular polyester chips, wherein the chemical formula of the nanoscale porous rare earth silicate is (LaaCebYcSmd) 2Si2O7 (at) KH550, a, b, c and d are more than 0 and less than 1, and a + b + c + d = 1. The fabric woven by the fibers is light and thin in texture, low in heat conductivity coefficient and high in tensile strength, and has excellent heat insulation and heat preservation effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional fibers, and in particular relates to a nano porous rare earth silicate thermal insulation fiber synthesized by a coprecipitation method and a preparation method thereof. Background Art

[0002] With the continuous prosperity of social economy and the evolution of modern lifestyle, people are increasingly interested in outdoor leisure activities, which not only reflects the improvement of quality of life, but also demonstrates the yearning for natural experience and health pursuit. As a result, consumers' expectations for functional outdoor textiles have increased significantly, especially products with excellent thermal insulation performance. They need to meet the needs of warmth while also taking into account comfort and durability.

[0003] In view of this, the development of a new type of fiber fabric that not only has excellent thermal insulation effect, but also ensures good tensile strength and excellent thermal insulation performance has become an urgent need in the industry. This type of fabric is designed to provide all-round protection for outdoor enthusiasts, so that they can still maintain physical comfort in severe cold or hot environments, thereby enhancing the overall experience of outdoor activities. However, the mainstream thermal insulation fabrics on the current market mostly rely on surface coating technology to achieve thermal insulation function. Although this method has achieved the expected effect to a certain extent, the coating treatment often causes the fabric texture to be heavy, and it is easily affected by environmental factors such as humidity and temperature changes during long-term use, resulting in reduced weather resistance, affecting the wearing experience and service life.

[0004] To overcome the above limitations, the research team is committed to exploring innovative solutions. Among them, thermal insulation fiber fabrics made of materials such as aerogel silica, glass microspheres and thermal expansion balls have shown great potential. Although these materials can theoretically provide excellent thermal insulation performance, their large particle size makes it difficult to carry out fine processing, which in turn affects the tensile strength of the fiber, limiting their wide application in actual products.

[0005] In order to address this challenge, in-depth research and technological innovation are particularly critical. Optimizing material formulations, improving processing technology, and developing new composite materials will be important ways to break through existing bottlenecks. By precisely controlling material particle size, enhancing inter-fiber bonding, and improving the overall structural stability of fabrics, it is expected that thermal insulation fiber fabrics with better performance and better market demand will be created, leading the innovation trend of the outdoor textile industry. Summary of the invention

[0006] In view of this, the present invention aims to propose a co-precipitation method for synthesizing nanoporous rare earth silicate thermal insulation fiber and a preparation method thereof, so as to solve the defects of the prior art such as complex rare earth silicate preparation process, high cost, high thermal conductivity of thermal insulation fiber, poor thermal insulation effect, and low fiber tensile strength.

[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0008] A nanoporous rare earth silicate thermal insulation fiber synthesized by a coprecipitation method is prepared by a melt spinning process from the following components by weight: 2-15 parts of nanoporous rare earth silicate and 85-98 parts of high molecular polyester chips; wherein the chemical formula of the nanoporous rare earth silicate is (La a Ce b Y c Sm d ) 2 Si 2 O 7 @KH550, 0<a,b,c,d<1, and a+b+c+d=1.

[0009] Furthermore, the nanoscale porous rare earth silicate is prepared by the following method:

[0010] 1) uniformly dispersing 2-10 parts by weight of a rare earth chloride salt in 2-10 parts by weight of deionized water to obtain a rare earth chloride salt solution;

[0011] 2) dissolving 1-5 parts by weight of sodium silicate and 0.1-3 parts by weight of a surfactant in 50-70° C. deionized water in sequence to obtain a sodium silicate solution;

[0012] 3) Pour 0.1-5 parts by weight of the surfactant solution into the rare earth chloride solution, then add an acidic solution to adjust the pH to between 2-4, and finally add the sodium silicate solution dropwise while stirring;

[0013] 4) filtering, washing and drying the system after the reaction to obtain a nano-scale porous rare earth silicate precursor;

[0014] 5) dispersing the nano-scale porous rare earth silicate precursor in anhydrous ethanol, adding a surface modifier for ultrasonic dispersion, and finally filtering and freeze-drying to obtain the nano-scale porous rare earth silicate.

[0015] Further, in step 1), the solid content of the rare earth chloride salt solution is 50-80% and the temperature is 50-70°C;

[0016] In step 3), the surfactant solution is poured into the rare earth chloride solution, the temperature is maintained at 50-70°C, and stirred for 60-90 minutes; after the sodium silicate solution is added dropwise, the reaction is continued for 3-5 hours;

[0017] In step 4), the drying temperature is 60-80°C;

[0018] In step 5), ultrasonic dispersion is performed for 30-60 minutes, and the freeze-drying temperature is -10°C to -50°C.

[0019] Furthermore, the rare earth chloride salt is a mixture of lanthanum chloride, yttrium chloride, samarium chloride and cerium chloride.

[0020] Further, the surfactant is one or a mixture of more than one of citric acid, sodium citrate, sodium lauryl sulfate, and ethylenediaminetetraacetic acid;

[0021] The acidic solution is a mixture of one or more of hydrochloric acid, oxalic acid, acetic acid, and citric acid, and the pH value of the acidic solution is 1;

[0022] The surface modifier is KH550.

[0023] Furthermore, the sodium silicate solution drop rate is 10-20 mL min -1 , the concentration of sodium silicate solution is 5-15mol / L.

[0024] Furthermore, the polymer polyester slice is one or more of polyethylene terephthalate, polybutylene terephthalate, polyamide, polyethylene, polyurethane, and polylactic acid.

[0025] The present invention also provides a method for preparing the nanoporous rare earth silicate thermal insulation fiber synthesized by the coprecipitation method as described above, the method comprising the following steps:

[0026] 1) mixing nano-scale porous rare earth silicate and polymer polyester chips uniformly, and then drying them in an oven to obtain functional polymer polyester chips with a water content of less than 300 ppm;

[0027] 2) putting the functional high molecular weight polyester chips obtained in step 1) into a twin-screw extruder for melt extrusion granulation to obtain thermal insulation masterbatch;

[0028] 3) The thermal insulation masterbatch obtained in step 2) is subjected to a melt spinning process to prepare a circular thermal insulation fiber.

[0029] Further, in step 1), the drying temperature is 65-90°C and the drying time is 8-15h;

[0030] In step 2), the temperature of melt extrusion is 150-350° C., and the extrusion speed is 100-300 r / min.

[0031] The present invention also provides an application of the nano porous rare earth silicate thermal insulation fiber synthesized by the coprecipitation method as described above in outdoor products, clothing, home furnishings and industrial textiles.

[0032] Compared with the prior art, the coprecipitation method for synthesizing nanoporous rare earth silicate thermal insulation fiber and the preparation method thereof described in the present invention have the following advantages:

[0033] (1) The nano-porous rare earth silicate described in the present invention is synthesized by a co-precipitation method. The method adjusts the reaction conditions such as the concentration (solid content) of the rare earth chloride solution, the addition of a surfactant, and the pH value of the reaction system to finally prepare the nano-porous rare earth silicate. The preparation method has a simple process, controllable particle size, large yield and high purity, and can be directly used for granulation and spinning.

[0034] 2) The nano-porous rare earth silicate described in the present invention not only has stable physical and chemical properties, large specific surface area, and low thermal conductivity, but is also an excellent thermal insulation material. In addition, the surface structure of the nano-porous rare earth silicate contains an organic-inorganic linker, which can form a strong bond with the polymer polyester chips, making it difficult to fall off, which is conducive to better exerting the thermal insulation effect.

[0035] 3) In the present invention, nano-porous rare earth silicate is blended with polymer polyester chips, and then melt-spinned to finally form thermal insulation fibers, which are knitted or weaved to form thermal insulation fabrics. Finally, the thermal conductivity, tensile strength and thermal insulation rate of the fabrics are tested. The thermal insulation fabrics are light and thin, have low thermal conductivity, high tensile strength and high thermal insulation rate, and have excellent thermal insulation effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0037] Figure 1 It is a schematic diagram of the reaction process of the present invention;

[0038] Figure 2 This is a SEM image of the nano-scale porous rare earth silicate prepared in Example 1 of the present invention;

[0039] Figure 3 This is the X-ray diffraction pattern of the nano-porous rare earth silicate prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0040] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] A nanoporous rare earth silicate thermal insulation fiber synthesized by a coprecipitation method is prepared by a melt spinning process from the following components in weight: 10 parts of nanoporous rare earth silicate and 90 parts of high molecular polyester chips; wherein the chemical formula of the nanoporous rare earth silicate is (La 0.25 Ce 0.25 Y 0.25 Sm 0.25 ) 2 Si 2 O 7 @KH550, high molecular weight polyester chips are 45 parts of polyethylene terephthalate and 45 parts of polybutylene terephthalate.

[0044] Wherein, the nano-scale porous rare earth silicate is prepared by the following method:

[0045] 1) Weigh lanthanum chloride, cerium chloride, yttrium chloride and samarium chloride in a molar ratio of 0.25:0.25:0.25:0.25, dissolve 6 parts of the mixture of rare earth chlorides in 4 parts of deionized water and disperse them uniformly to obtain a rare earth chloride solution with a solid content of 60% and a temperature of 60° C.;

[0046] 2) dissolving 2 parts of sodium silicate and 1 part of surfactant sodium citrate in the same part of 60° C. deionized water to obtain a sodium silicate solution;

[0047] 3) Pour 1 portion of surfactant sodium citrate solution into rare earth chloride solution, maintain the temperature at 60°C, and stir for 60 minutes; then add pH=1 acidic solution to adjust the solution pH to 3, and finally add sodium silicate solution drop by drop while stirring for 4 hours. The concentration of sodium silicate solution is 10 mol / L, and the dropping speed is 15 mL·min -1 ; The acidic solution is a mixed solution of hydrochloric acid, oxalic acid, acetic acid and citric acid with a pH value of 1;

[0048] 4) The reaction system is filtered, washed, and dried at 60° C. for 12 hours to obtain a nano-scale porous rare earth silicate precursor;

[0049] 5) Disperse the nanoporous rare earth silicate precursor in anhydrous ethanol and add the surface modifier KH550 (NH 2 -(CH 2 ) 3 -Si-(OCH 2 CH 3 ) 3 ) was ultrasonically dispersed for 60 minutes, and finally filtered and freeze-dried at -30℃ to obtain nano-porous rare earth silicate (La 0.25 Ce 0.25 Y 0.25 Sm0.25 ) 2 Si 2 O 7 @KH550.

[0050] The method for preparing the nanoporous rare earth silicate thermal insulation fiber synthesized by the coprecipitation method comprises the following steps:

[0051] 1) mixing nano-scale porous rare earth silicate and polymer polyester chips uniformly, and then drying them in an oven at 80° C. for 12 hours to obtain functional polymer polyester chips with a water content of less than 300 ppm;

[0052] 2) putting the functional polymer polyester chips obtained in step 1) into a twin-screw extruder, performing melt extrusion granulation at 270° C., the strand water temperature is 70° C., the extrusion speed is 200 r / min, and finally obtaining thermal insulation masterbatch;

[0053] 3) drying the thermal insulation masterbatch obtained in step 2) at 120° C. for 12 hours to make the moisture content less than 200 ppm, and preparing a round thermal insulation fiber through a melt spinning process at a spinning temperature of 270° C. and a winding speed of 400 m / min;

[0054] 4) Finally, the thermal insulation fiber fabric is made by weaving or knitting.

[0055] Figure 1 It is a schematic diagram of the reaction process of the present invention, Figure 2 This is a SEM image of the nano-scale porous rare earth silicate prepared in this example. It can be seen from the image that the surface of the nano-scale porous rare earth silicate is covered with a porous structure. Figure 3 This is the X-ray diffraction diagram of the nano-porous rare earth silicate prepared in this example. From the figure, we can see that the diffraction peaks of the powder we prepared are consistent with (La 0.25 Ce 0.25 Y 0.25 Sm 0.25 ) 2 Si 2 O 7 The standard card is consistent with the standard card, that is, the (La 0.25 Ce 0.25 Y 0.25 Sm 0.25 ) 2 Si 2 O 7 , and the diffraction peak is sharp, indicating good crystallinity and stable physical and chemical properties.

[0056] Example 2

[0057] On the basis of the above-mentioned Example 1, the rare earth chloride salts used to prepare the nano-porous rare earth silicate are lanthanum chloride, cerous chloride, yttrium chloride and samarium chloride in a molar ratio of 0.35:0.2:0.3:0.15, the surfactant is sodium dodecyl sulfate, and the rest is the same as in Example 1.

[0058] Finally, the thermal insulation fiber fabric is made by weaving or knitting.

[0059] Example 3

[0060] On the basis of the above-mentioned Example 1, the rare earth chloride salts used to prepare the nano-porous rare earth silicate are lanthanum chloride, cerous chloride, yttrium chloride and samarium chloride in a molar ratio of 0.3:0.2:0.4:0.1, the surfactant is ethylenediaminetetraacetic acid, and the rest are the same as in Example 1.

[0061] Finally, the thermal insulation fiber fabric is made by weaving or knitting.

[0062] Example 4

[0063] On the basis of the above-mentioned Example 1, the rare earth chloride salts used to prepare the nano-porous rare earth silicate are lanthanum chloride, cerous chloride, yttrium chloride and samarium chloride in a molar ratio of 0.4:0.1:0.4:0.1, the surfactant is citric acid, and the rest is the same as in Example 1.

[0064] Finally, the thermal insulation fiber fabric is made by weaving or knitting.

[0065] Comparative Example 1

[0066] The difference from Example 1 is that the usage amounts of nano-porous rare earth silicate and high molecular polyester chips are different, 1 part of nano-porous rare earth silicate, 49.5 parts of polyethylene terephthalate powder and 49.5 parts of polybutylene terephthalate powder are mixed.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that the usage amounts of nano-porous rare earth silicate and high molecular polyester chips are different, 20 parts of nano-porous rare earth silicate, 40 parts of polyethylene terephthalate powder and 40 parts of polybutylene terephthalate powder are mixed.

[0069] Comparative Example 3

[0070] The difference from Example 1 is that the reaction temperatures of step 2) and step 3) in preparing the nano-scale porous rare earth silicate are different:

[0071] 2) dissolving 2 parts of sodium silicate and 1 part of surfactant sodium citrate in 90° C. deionized water to obtain a sodium silicate solution;

[0072] 3) Pour the surfactant sodium citrate solution into the rare earth chloride solution at 80°C, maintain 90°C, stir for 60 minutes, then add acidic solution to adjust the pH to 3, and finally add sodium silicate solution drop by drop while stirring, and react for 4 hours after the addition is completed.

[0073] Comparative Example 4

[0074] The difference from Example 1 is that, in the preparation of the nano-scale porous rare earth silicate, an acidic solution is added in step 3) to adjust the pH to 1.

[0075] Comparative Example 5

[0076] The difference from Example 1 is that the rare earth silicate is prepared by solid phase grinding method. The specific preparation method is as follows:

[0077] 1) Weigh lanthanum oxide, cerium oxide, yttrium oxide, samarium oxide and silicon oxide in a molar ratio of 0.25:0.25:0.25:0.25:2, mix well and add deionized water to make the solid content 60%;

[0078] 2) Pour the material weighed in step 1) into a ball mill, mill it at a speed of 500 r / min for 8 hours, take it out, pour it into a sand mill, and grind it to a slurry particle size of 300 nm. Filter it, wash it, and dry it at 60° C. for 12 hours to obtain a nano rare earth silicate precursor;

[0079] 3) Disperse the nano rare earth silicate precursor in anhydrous ethanol and add an appropriate amount of surface modifier KH550 (NH 2 -(CH 2 ) 3 -Si-(OCH 2 CH 3 ) 3 After ultrasonic dispersion for 60 minutes, the nanoscale (La 0.25 Ce 0.25 Y 0.25 Sm 0.25 ) 2 Si 2 O 7 @KH550.

[0080] 4) Nanoscale (La 0.25 Ce 0.25 Y 0.25 Sm 0.25 ) 2 Si 2 O 7 @The preparation method and addition ratio of KH550 modified thermal insulation fiber are the same as those in Example 1.

[0081] Comparative Example 6

[0082] The difference from Example 1 is that the rare earth chloride salt is lanthanum chloride, cerium chloride, and yttrium chloride in a molar ratio of 1 / 3:1 / 3:1 / 3, and the nano-porous rare earth silicate is (La 1 / 3 Ce 1 / 3 Y 1 / 3 ) 2 Si 2 O 7 .

[0083] Comparative Example 7

[0084] The difference from Example 1 is that the rare earth chloride salt is cerium chloride, yttrium chloride, and samarium chloride in a molar ratio of 1 / 3:1 / 3:1 / 3, and the nano-porous rare earth silicate is (Ce 1 / 3 Y 1 / 3 Sm 1 / 3 ) 2 Si 2 O 7 .

[0085] Comparative Example 8

[0086] The difference from Example 1 is that the rare earth chloride salt is lanthanum chloride, yttrium chloride, and samarium chloride in a molar ratio of 1 / 3:1 / 3:1 / 3, and the nano-porous rare earth silicate is (La 1 / 3 Y 1 / 3 Sm 1 / 3 ) 2 Si 2 O 7 .

[0087] Comparative Example 9

[0088] The difference from Example 1 is that the rare earth chloride salt is lanthanum chloride, cerium chloride, yttrium chloride, and samarium chloride in a molar ratio of 0.5:0.5:0.5:0.5, and the final product (La 0.5 Ce 0.5 Y 0.5 Sm 0.5 ) 2 Si 2 O 10 .

[0089] Comparative Example 10

[0090] The difference from Example 1 is that the concentration of the rare earth chloride solution is different, 9 parts of rare earth chloride are dissolved in 1 part of deionized water, and the solid content is 90%.

[0091] Comparative Example 11

[0092] The difference from Example 1 is that no surfactant is added when preparing the nano-scale porous rare earth silicate.

[0093] Blank fabric

[0094] That is, no nano-porous rare earth silicate is added to the fiber fabric. The specific preparation method is as follows: (1) 50 parts of polyethylene terephthalate powder and 50 parts of polybutylene terephthalate powder are weighed according to the mass ratio, mixed evenly, and then dried in an oven at 80° C. for 12 hours to obtain a functional polymer polyester chip with a water content of less than 300 ppm;

[0095] (2) The mixed powder obtained in step (1) was put into a twin-screw extruder and melt-extruded and granulated at 270°C, the strand water temperature was 70°C, and the extrusion speed was 200r /

[0096] min, and finally the masterbatch is obtained;

[0097] (3) The masterbatch obtained in step (2) is dried at 120° C. for 12 hours to reduce the moisture content to less than 200 ppm, and a round thermal insulation fiber is prepared by a melt spinning process at a spinning temperature of 270° C. and a winding speed of 400 m / min, and a fiber fabric is made by weaving or knitting.

[0098] The specific surface area of ​​the nano-porous rare earth silicate prepared in Examples 1-4 was tested, and the thermal insulation fiber fabric prepared therefrom was tested for thermal conductivity, tensile strength and thermal insulation rate. The results are shown in Table 1.

[0099] Table 1 Comparison of performance indicators of Examples 1-4 and blank fabrics

[0100]

[0101]

[0102] As can be seen from Table 1, the nanoporous silicate prepared by coprecipitation has a large specific surface area, which can reach up to 488.51 m 2 / g, the larger the specific surface area, the larger the surface area of ​​the still air layer, which is more conducive to improving the thermal insulation performance of the fiber fabric. The main indicators for measuring thermal insulation fibers and fabrics are thermal conductivity and thermal insulation rate. The lower the thermal conductivity, the higher the thermal insulation rate, and the better the thermal insulation of the fabric. Compared with the blank fabric, Examples 1-4 all have extremely low thermal conductivity and high thermal insulation rate, reflecting excellent thermal insulation. In addition, adding inorganic components to the fiber generally leads to incompatibility, resulting in low tensile strength of the fiber and fabric, easy tearing, and inability to be used. In Examples 1-4, the surface of the nanoporous rare earth silicate is modified so that it can be connected with the inorganic component and compatible with the organic matrix, which can effectively improve the tensile strength of the fabric. By comparing the tensile strength of Examples 1-4 and the blank fabric, it can be seen that when the amount of nanoporous rare earth silicate added reaches 10 parts, the tensile strength of the fabric is basically the same as that of the pure fiber fabric.

[0103] The silicates prepared in Comparative Examples 1-11 were tested for specific surface area, and Example 1 and the comparative examples were tested for thermal conductivity, thermal conductivity coefficient and heat preservation. The test results are shown in Table 2.

[0104] Table 2 is a comparison of the performance indicators of each comparative example

[0105]

[0106]

[0107] By comparing the performance of Example 1 with that of Comparative Examples 1-2, it can be seen that when the amount of nanoporous silicate added is 10 parts, the thermal insulation effect of the fiber fabric is the best. When the amount added is 1 part, the content of nanoporous rare earth silicate in the fiber is low, which is not enough to significantly improve the thermal insulation of the fiber fabric. If too much is added, agglomeration may occur, resulting in uneven distribution of rare earth silicate, which ultimately leads to reduced thermal insulation of the fiber fabric. In addition, if too much is added, the fibers will agglomerate into large particles, which will weaken the tensile strength of the fibers and limit their application.

[0108] By comparing the performance of Example 1 with that of Comparative Example 3, it can be seen that by adjusting the reaction temperature, a porous rare earth silicate with a larger particle size (smaller specific surface area) can be obtained, and the thermal insulation fiber prepared therefrom has poor thermal insulation and tensile strength. This is because the large-particle porous silicate has a smaller distribution amount and more voids at the same addition amount. In addition, the large-particle rare earth silicate has a small specific surface area and a small static air layer area. Under the influence of these two factors, its thermal insulation and tensile strength are both poor; the silicon source in the nano-scale porous rare earth silicate is sodium silicate, which will be electrolyzed into Na + and SiO 3 2+ , SiO 3 2+ Easy and H + The reaction generates H2 SiO 3 , reducing the SiO in the solution 3 2+ , thereby reducing the yield of rare earth silicate.

[0109] In Comparative Example 4, the solution pH is 1, and H + Too high content will make SiO 3 2+ The content becomes lower, which in turn reduces the production yield.

[0110] Comparative Example 5 is a nano rare earth silicate prepared by a solid phase grinding method. Although the preparation process is relatively simple and only requires grinding according to the ratio, the preparation process is time-consuming and energy-consuming. The rare earth silicate finally obtained has a very low specific surface area. The thermal insulation fiber prepared in this way has a high thermal conductivity and a low thermal insulation rate.

[0111] Comparing the performance of Example 1 with Comparative Examples 6-8, it can be seen that Comparative Examples 6-8 are all ternary nanoporous silicates, and their specific surface areas are similar to those of multi-element nanoporous silicates, but their thermal insulation performance is poor. This is because the multi-element nanoporous rare earth silicates contain a variety of rare earth ions, which increase the mass disorder and bonding disorder of the material, thereby reducing the thermal conductivity and improving the thermal insulation performance.

[0112] In Comparative Example 9, adjusting the proportion of rare earth elements in rare earth silicates may affect the formation and stability of pores on the surface of the reaction product. Excessive amounts of a certain element may fill or destroy these pores, thereby reducing the porosity of the material and thus weakening its thermal insulation performance. In addition, an excess of a certain element may also cause phase separation inside the material, forming new phases that are different from the main material. These new phases may have different thermal properties, thereby affecting the thermal insulation effect of the overall material. Phase separation can also lead to a decrease in the uniformity of the material, thereby affecting its long-term performance.

[0113] In Comparative Example 10, the concentration of the rare earth chloride solution is increased. Under high concentration conditions, rare earth ions may be locally oversaturated, which may easily produce by-products or irregular precipitation, thereby affecting product purity. In addition, under high concentration conditions, the nucleation rate and growth rate will be accelerated, which may lead to the formation of larger particle precipitates. These large particles have a smaller specific surface area, thereby reducing the thermal insulation effect. In addition, when these large particles are added to the fiber, due to the larger particle size, the fiber may be more easily broken, thereby reducing the tensile strength of the fiber.

[0114] In Comparative Example 11, no surfactant was added during the reaction, and the rare earth silicate finally generated was larger in size, with serious agglomeration between the particles and unstable surface properties, resulting in a small specific surface area and low fiber tensile strength.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method, characterized in that: The nanoporous rare earth silicate is prepared by melt spinning process by the following weight parts: 2-15 parts of nanoporous rare earth silicate and 85-98 parts of high molecular polyester chips; wherein the chemical formula of the nanoporous rare earth silicate is (La a Ce b Y c Sm d )2Si2O7@KH550, 0<a,b,c,d<1, and a+b+c+d=1.

2. The nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method according to claim 1, characterized in that: The nano-scale porous rare earth silicate is prepared by the following method: 1) uniformly dispersing 2-10 parts by weight of a rare earth chloride salt in 2-10 parts by weight of deionized water to obtain a rare earth chloride salt solution; 2) dissolving 1-5 parts by weight of sodium silicate and 0.1-3 parts by weight of a surfactant in 50-70° C. deionized water in sequence to obtain a sodium silicate solution; 3) Pour 0.1-5 parts by weight of the surfactant solution into the rare earth chloride solution, then add an acidic solution to adjust the pH to between 2-4, and finally add the sodium silicate solution dropwise while stirring; 4) filtering, washing and drying the system after the reaction to obtain a nano-scale porous rare earth silicate precursor; 5) dispersing the nano-scale porous rare earth silicate precursor in anhydrous ethanol, adding a surface modifier for ultrasonic dispersion, and finally filtering and freeze-drying to obtain the nano-scale porous rare earth silicate.

3. The nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method according to claim 2, characterized in that: In step 1), the solid content of the rare earth chloride solution is 50-80% and the temperature is 50-70° C.; In step 3), the surfactant solution is poured into the rare earth chloride solution, the temperature is maintained at 50-70°C, and stirred for 60-90 minutes; after the sodium silicate solution is added dropwise, the reaction is continued for 3-5 hours; In step 4), the drying temperature is 60-80°C; In step 5), ultrasonic dispersion is performed for 30-60 minutes, and the freeze-drying temperature is -10°C to -50°C.

4. The nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method according to claim 2, characterized in that: The rare earth chloride salt is a mixture of lanthanum chloride, yttrium chloride, samarium chloride and cerium chloride.

5. The nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method according to claim 2, characterized in that: The surfactant is one or a mixture of citric acid, sodium citrate, sodium lauryl sulfate, and ethylenediaminetetraacetic acid; The acidic solution is a mixture of one or more of hydrochloric acid, oxalic acid, acetic acid, and citric acid, and the pH value of the acidic solution is 1; The surface modifier is KH550.

6. The nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method according to claim 2, characterized in that: The sodium silicate solution drop rate is 10-20mL·min -1 , the concentration of sodium silicate solution is 5-15mol / L.

7. The nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method according to claim 1, characterized in that: The high molecular polyester slice is one or more of polyethylene terephthalate, polybutylene terephthalate, polyamide, polyethylene, polyurethane and polylactic acid.

8. A method for preparing nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: 1) mixing nano-scale porous rare earth silicate and polymer polyester chips uniformly, and then drying them in an oven to obtain functional polymer polyester chips with a water content of less than 300 ppm; 2) putting the functional high molecular weight polyester chips obtained in step 1) into a twin-screw extruder for melt extrusion granulation to obtain thermal insulation masterbatch; 3) The thermal insulation masterbatch obtained in step 2) is subjected to a melt spinning process to prepare a circular thermal insulation fiber.

9. The method for preparing nanoporous rare earth silicate thermal insulation fiber synthesized by coprecipitation method according to claim 8, characterized in that: In step 1), the drying temperature is 65-90°C and the drying time is 8-15h; In step 2), the temperature of melt extrusion is 150-350° C., and the extrusion speed is 100-300 r / min.

10. Use of the nanoporous rare earth silicate thermal insulation fiber synthesized by the coprecipitation method as claimed in any one of claims 1 to 7 in outdoor products, clothing, home furnishings and industrial textiles.

Citation Information

Patent Citations

  • Nanoscale rare earth silicate powder material and applications thereof

    CN111017982A

  • Rare-earth-based warm-keeping composite fiber as well as preparation method and application thereof

    CN114525595A

  • High-temperature-resistant ultrahigh-porosity high-entropy rare earth silicate and preparation method thereof

    CN117285338A

  • Rare-earth-based cooling and heat-insulating profiled fiber and preparation method thereof

    CN117468120A

  • High-entropy rare earth silicate ceramic nano-powder as well as preparation method and application thereof

    CN117486610A